Association of Pretreatment Serum Indirect Bilirubin Levels With Prognostic and Therapeutic Value in Patients With Newly Diagnosed Acute Myeloid Leukemia - Chunfang Kong; Linhui Hu; Ling Zhang; Hongbo Cheng; Qilin Lu; Anna Li; Bo Ke; Wenting Cui; Huixia Zhang; Mei Wu; Qingqing Zhu; Chenghao Jin; et al. (Cancer Medicine, 2025)
ABSTRACT Background Bilirubin has anti‐inflammatory, antioxidant, and anti‐cancer properties, with an inverse relationship between its levels and cancer risk and prognosis. However, the prognostic value of serum bilirubin in acute myeloid leukemia (AML) remains uncertain. Methods This retrospective study analyzed pretreatment serum total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL) in 284 AML patients and 316 healthy controls. The prognostic significance of serum bilirubin levels was determined using the Kaplan–Meier method and Cox proportional hazards model. Results Pretreatment TBIL and IBIL levels were significantly lower in AML patients compared to controls. TBIL and IBIL levels were significantly higher in the CR/CRh/CRi group than in the non‐CR/CRh/CRi group and increased significantly after chemotherapy. Elevated pretreatment TBIL and IBIL were associated with longer overall survival (OS) (p < 0.05) and progression‐free survival (PFS) (p < 0.05). Pretreatment IBIL was an independent prognostic factor for OS (hazard ratio [HR], 0.47; 95% confidence interval [CI] 0.28–0.79; p < 0.05) and PFS (HR, 0.53; 95% CI 0.33–0.85; p < 0.05). Conclusion Elevated pretreatment IBIL levels are correlated with improved OS and PFS, acting as an independent favorable prognostic indicator for AML.